Implementation of Lesson Study as an Innovative Professional Development Model Among Malaysian School Teachers - Mohd Hasani Dali; Chiew Chin Mon; Lim Chap Sam (Malaysian Journal of Learning and Instruction, 2016)
Purpose â€“ This qualitative study explored the implementation of Lesson Study, a kind of teacher-directed and bottom-up approach of the Japanese model of teacher professional development in the Malaysian education context. It seeks to answer the question of how implementation of lesson study as an innovative professional development model among Malaysian school teachers influences teachersâ€™ pedagogical content knowledge, and what school-based factors support or hinder the implementation of lesson study in the Malaysian context.